Production of Several Types of Vegetables in the Composition of the Growing Media Cultivated in a Verticulture - Ramdan Hidayat; Purnomo Edi Sasongko; Nora Augustien (Nusantara Science and Technology Proceedings, 2021)
Mitigation of the risk of decreasing food security in urban areas can be done through the use of yardland through urban agriculture which is currently being carried out by urban communities since staying at home is one of the family's independent food solutions by cultivating short-lived vegetables (3-4 weeks) with a multilevel agricultural cultivation system. or ver-tical. The purpose of this study was to determine the composition of the growing media which resulted in the best production of three types of veg-etable crops cultivated vertically. The research was carried out in the ex-perimental garden of the Faculty of Agriculture, UPN "Veteran" Jawa Timur, Surabaya which was arranged in a completely randomized design (CRD), and was repeated 3 times. Factor 1 is the Composition of Planting Media which consists of 4 kinds of composition, namely: Soil, Compost, and Manure, namely: 1:1:1 (K1); 1:1:2 (K2); 1:2;1 (K3), and 1:2:2 (K4). The second factor is the type of vegetables (J), which consists of 3 types, namely: Pakcoy Mustard Plants (J1), Kangkung Plants (J2), and Red Spinach Plants (J3). The results showed that there was a significant interaction between plant height and vegetable production, where the K4J3 combination produced the highest production and was significant different with other treatment combinations.